In the eye and mind of the beholder: The effects of familiarisation on the perception of atypical infant facial configurations. - Benjamin W Hunt; Leonardo De Pascalis (PLoS ONE)
Perception of infant faces plays a crucial role in adult-infant caretaking behaviour, with adults being found to demonstrate a reliable attraction towards infant faces over other stimuli. When affected by a congenital facial malformation such as cleft lip and/or palate, however, adults' visual scanning patterns and subjective appraisal of these faces have been found to be adversely affected. Little past work has explored how an observer's prior experience with this specific malformation might play a role in the perception of cleft-affected infant faces. To this end, two groups of adult female participants were recruited and presented with 48 images of infant faces (24 typical, 24 cleft-affected) with one group subjected to novel, purpose-built familiarisation training, where participants were exposed to infant cleft lip/palate related visual and informational stimuli prior to testing (n = 43). Eye gaze patterns and subjective "cuteness" ratings from this group were compared with an age matched control group which received no training (n = 41). No between group differences were found for "cuteness" ratings or eye gaze patterns to the cleft-affected mouth area in isolation, however, a significant negative relationship was found between gaze duration to the mouth region of cleft-affected images and subjective "cuteness" ratings, for control participants only. Notably, this relationship was not observed for the familiarised participants, suggesting their modified prior experience attenuated the effect that visual processing had on subjective appraisal of cleft-affected faces, when these two factors were assessed in tandem. Our findings suggest it is possible to attenuate the typically observed aversive behaviour towards cleft-affected infant faces. This may have implications for clinical practice concerned with supporting adult caretaking of malformation-affected infants and policies related to increasing positive perception of congenital facial disfigurement.